Genesis of the Shibaogou Mo–Pb–Zn deposit in the Luanchuan ore district, China: Constraints from geochronology, fluid inclusion, and H–O–S–Pb isotopes - Xu, Yunchou; Wang, Gongwen; Gao, Meng; Yang, Wangdong; Yang, Shuren; Yun, Hui; Wu, Peijian; Guo, Nana; Feng, Yantao (Frontiers in Earth Science, 2023)
The Shibaogou deposit is located in the Luanchuan ore district within the East Qinling orogenic belt (EQOB), central China, which is a newly discovered Mo–Pb–Zn skarn deposit. The skarn and Mo–Pb–Zn ore bodies are mostly hosted in the contact zones between the Shibaogou porphyritic granite and carbonaceous sedimentary rocks from the Luanchuan and Guandaokou sets. A study combined of geochronology, fluid inclusion (FI), and stable isotopes was performed to constrain the mineralization age, source of ore materials, and the origin and evolution of the ore-forming fluids and their relationship with the subduction of the Paleo-Pacific Plate. The mineralization process includes skarn and quartz–sulfide episodes, which has four stages: skarn (I), quartz–molybdenite (II), quartz–galena–sphalerite (III), and quartz–calcite (IV). Molybdenite Re-Os dating suggests that the deposit was formed in the Late Jurassic (147.4 ± 7.2 Ma). Reportedly, there are five primary types of fluid inclusions: L-type, V-type, H-type, S-type, and C-type. In the skarn stage, coexisting H-type (35.58 wt%–46.05 wt% NaCl equiv.) and low-salinity V-type (0.35 wt%–5.7 wt% NaCl equiv.) fluid inclusions show similar homogenization temperatures, which suggests that fluid boiling occurred at 513–550°C and 580–650 bar (2.19–2.45 km). In the quartz–molybdenite stage, the homogenization temperatures of L-type, V-type, minor H-type, and S-type fluid inclusions indicate continued fluid boiling at 324–387°C and 180–250 bar (0.49–0.94 km). In the quartz–galena–sphalerite stage, a fewer number of coexisting V-type and L-type fluid inclusions in quartz shows different salinities with similar homogenization temperatures, indicating that they are trapped at 303–347°C and <150 bar in the boiling process (<0.56 km hydrostatic depth). The minor primary L-type fluid inclusions that have lower salinities of 0.88 wt%–11.34 wt% NaCl equiv were observed in quartz and calcite in the quartz–calcite stage; in addition, their homogenization temperatures are 103–247°C (typical post-ore conditions). This study found that the ore-forming fluids at the Shibaogou deposit were dominantly magmatic water at the early stage, with input of atmospheric water during fluid evolution, with δ18Ofluid values from −1.168‰ to 8.997‰ and δ18Dfluid values from −106.5‰ to −79.9‰, based on the O and H isotope data from garnet, quartz, and calcite. Furthermore, the S isotopic compositions were measured ranging from 0.8‰ to 14.7‰, and it demonstrated that the ore-forming fluid was mainly derived from magmatic sources. The relatively homogeneous Pb isotopic compositions are similar to those of Shibaogou granite porphyry, which demonstrated that the ore-forming materials were mainly derived from magmatic sources. Molybdenite was precipitated as a result of fluid–rock interactions and fluid boiling, and the galena and sphalerite were precipitated as a result of the decreasing temperature. The subduction of the Paleo-Pacific plate has a critical impact on the complex evolution of ore formation in the Shibaogou skarn deposit in EQOB.